Pelatihan Business Plan untuk Peningkatan Kapasitas Wirausaha Muda melalui Program Boot Camp Dinas Koperasi dan UMKM Provinsi Sumatera Utara - Hasbullah, Amilia; Hermanto, Ahmad; Wibowo, Imam; Indra, Harry (Journal Of Human And Education (JAHE), 2024)
The capacity to design a Business Plan is crucial for entrepreneurs to initiate and advance their enterprises. Business Plans are often considered as sophisticated due to restricted access and insufficient knowledge for interpretation and implementation. The Board of Cooperative and MSME North Sumatra Province, that involved fellow of Krisnadwipayana University, is conducting Boot Camp activities that include a series of capacity-building programs for young entrepreneurs, commencing with Business Plan training as the initial phase of the program. This initiative seeks to improve the capacity of young entrepreneurs in North Sumatra to develop efficient and pragmatic Business Plans. This activity fosters active learning, facilitates constructive discussions, and allows each participant to model the development of a Business Plan. Twenty-five chosen young entrepreneurs from North Sumatra Province participated in the event that occurred over four whole days. The structured Business Plan preparation curriculum equips participants with fundamental and technical abilities, encompassing market analysis, financial forecasting, marketing tactics, and operational planning. The workshop results indicate that participants significantly enhanced their comprehension of their business, established collaborative networks, and identified future possibilities and challenges for their enterprises. The outcome of this exercise highlights the significance of ongoing practical knowledge training to empower young entrepreneurs, thereby augmenting their future capabilities. Keywords: Young Entrepreneurs, Business Plan, Capacity Building